Buddha : an enlightened life - Moore, Kieron (Campfire heroes., 2017)
Offers a graphic-novel retelling of Siddhartha Gautam as he leaves the castle he was raised in to find enlightenment. After many years on a spiritual journey, Siddhartha returns as Gautam Buddha, thus beginning centuries of religious thought across the world.